Uwarunkowania stronnego zróZnicowania dokLadnosci ruchów u wysoko zaawansowanych zawodników uprawiajAcych rozmaite dyscypliny sportowe - Starosta, W. (Medycyna sportowa, 2001)
Precision of movements is one of the most essential components of sports technique. Maintaining a high precision of movements throughout the competition, and especially in its final phase, is frequently the key factor to success. However, the importance of movement precision has not been adequately reflected in the research, and this applies even more strongly to the lateral differentiation of movements. Thus, the aim of this study was to relate the lateral differentiation to the sport practised, and to determine the effect of physical load on the lateral differentiation of movement precision in various sports. The study was conducted on 135 athletes, mostly members of National Representations in judo, kayaking, ski jumping, Graeco-Roman wrestling sailing, windsurfing, rowing and figure skating. The ability to differentiate, without visual control, the movement amplitude and muscle tension of limbs, the method of Schulte, Puni and Starosta, and appropriate equipment (kinesthesiometer with goniometers and a tensodynamometer) were used. The specificity of given sport, expressed by the dominance of symmetric or asymmetric movements, was responsible for the laterality or ambidexterity regarding the precision of kinaesthetic perceptions. Physical loads induced differences in the movement precision of the left and right upper limbs in wrestlers, sailors and windsurfers. A higher precision of reproducing movements of a preset amplitude was noted for the right hand before the load, and left hand - following the load. The same was true for reproducing muscle strength (tension) by rowers, sailors and windsurfers.